2023
DOI: 10.1039/d3bm00515a
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical characterization of a fibrinogen–blood hydrogel for human dental pulp regeneration

Sofia Silvia Piglionico,
Bela Varga,
Orsolya Pall
et al.

Abstract: In dental practice, Regenerative Endodontic Treatment (RET) is applied as an alternative to classical endodontic treatment of immature necrotic teeth. This procedure, also known as dental pulp revitalization, relies on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Fibrinogen requires the addition of thrombin for polymerization and since blood contains thrombin, we can just induce blood to mix with the cell-laden fibrinogen. The gel polymerized, as in a published report (Piglionico et al 2023) and in our in vitro tube study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Fibrinogen requires the addition of thrombin for polymerization and since blood contains thrombin, we can just induce blood to mix with the cell-laden fibrinogen. The gel polymerized, as in a published report (Piglionico et al 2023) and in our in vitro tube study.…”
Section: Discussionmentioning
confidence: 64%
“…Fibrin gel has been widely used or proposed as a scaffold for tissue regeneration (Hubbell 2003;Hong and Stegemann 2008;Janmey et al 2009), including its use for cell-based pulp regeneration (Parmar et al 2020;Piglionico et al 2023). Although collagen hydrogel for cell-based pulp regeneration has shown success in large animal models and human trials (Nakashima et al 2017;Zhu et al 2018;Nakashima et al 2019Nakashima et al , 2022, our in vitro data indicated that even after DPSCs had differentiated into EC-like cells, tremendous contraction still occurred in collagen gels (Appendix Figs.…”
Section: Discussionmentioning
confidence: 90%